Individual flowering phenology shapes plant–pollinator interactions across ecological scales affecting plant reproduction. Issue 1 (4th January 2023) - Labonté, Audrey; Monticelli, Lucie S.; Turpin, Mélinda; Felten, Emeline; Laurent, Emilien; Matejicek, Annick; Biju‐Duval, Luc; Ducourtieux, Chantal; Vieren, Eric; Deytieux, Violaine; Cordeau, Stéphane; Bohan, David; et al.
Abstract: The balance of pollination competition and facilitation among co‐flowering plants and abiotic resource availability can modify plant species and individual reproduction. Floral resource succession and spatial heterogeneity modulate plant–pollinator interactions across ecological scales (individual plant, local assemblage, and interaction network of agroecological infrastructure across the farm). Intraspecific variation in flowering phenology can modulate the precise level of spatio‐temporal heterogeneity in floral resources, pollen donor density, and pollinator interactions that a plant individual is exposed to, thereby affecting reproduction. We tested how abiotic resources and multi‐scale plant–pollinator interactions affected individual plant seed set modulated by intraspecific variation in flowering phenology and spatio‐temporal floral heterogeneity arising from agroecological infrastructure. We transplanted two focal insect‐pollinated plant species ( Cyanus segetum and Centaurea jacea, n = 288) into agroecological infrastructure (10 sown wildflower and six legume–grass strips) across a farm‐scale experiment (125 ha). We applied an individual‐based phenologically explicit approach to match precisely the flowering period of plant individuals to the concomitant level of spatio‐temporal heterogeneity in plant–pollinator interactions, potential pollen donors, floral resources, and abiotic conditions (temperature, water, and nitrogen). Individual plant attractiveness, assemblage floral density, and conspecific pollen donor density ( C. jacea ) improved seed set. Network linkage density increased focal species seed set and modified the effect of local assemblage richness and abundance on C. segetum . Mutual dependence on pollinators in networks increased C. segetum seed set, while C. jacea seed set was greatest where both specialization on pollinators and mutual dependence was high. Abiotic conditions were of little or no importance to seed set. Intra‐ and interspecific plant–pollinator interactions respond to spatio‐temporal heterogeneity arising from agroecological management affecting wild plant species reproduction. The interplay of pollinator interactions within and between ecological scales affecting seed set implies a co‐occurrence of pollinator‐mediated facilitative and competitive interactions among plant species and individuals. Abstract : Using a farm‐scale experiment we investigated how intraspecific variation in flowering phenology and spatial heterogeneity in floral resources affected wild plant reproduction by modifying plant–pollinator interactions at the scale of the plant individual, the local assemblage, and the interaction network of agroecological infrastructures across the farm. We applied an original individual‐centered approach that ensured the spatio‐temporal variation in predictors of seed set (floral resources, pollinator activity, and interaction topology) matched exactly each individual plant's flowering period. These phenologically explicit models revealed that individual plant seed set in our two focal plant species ( Cyanus segetum and Centaurea jacea ) was influenced by patterns in plant–pollinator diversity and network structure that imply a co‐occurrence of pollinator‐mediated facilitative and competitive interactions operating within and between ecological scales. Icons sourced from: https://thenounproject.com/CC BY‐NC‐ND 2.0: (lluisa Iborra, Yu Luck, Les vieux garçons, Gan Khoon Lay, Blair Adams, Nareerat Jaikaew, and Prosymbols) and https://www.shutterstock.com (a free trial). Résumé: L'équilibre des relations de compétition et de facilitation entre plantes pour la pollinisation et la disponibilité des ressources abiotiques affectent le succès reproducteur des espèces et des individus de plantes. La succession temporelle et l'hétérogénéité spatiale des ressources florales modifient les interactions plantes‐pollinisateurs à différentes échelles écologiques (individu végétal, assemblage plantes‐pollinisateurs local, réseau d'interactions des infrastructures écologiques à travers la ferme). Les variations intraspécifiques de phénologie de floraison peuvent moduler le succès reproducteur individuel en déterminant le niveau d'hétérogénéité spatio‐temporelle de densité de donneurs de pollen, des interactions plantes‐pollinisateurs et des ressources florales auxquelles un individu de plante est exposé. Nous avons mené une expérimentation pour tester comment la production de graines des plantes sauvages est affectée par les interactions plantes‐pollinisateurs à différentes échelles écologiques, ces interactions étant modulées par la phénologie florale et l'hétérogénéité spatio‐temporelle des ressources florales (découlant des infrastructures agroécologiques). Nous avons transplanté 144 individus de deux espèces végétales entomophiles ( Cyanus segetum et Centaurea jacea ) dans des infrastructures agroécologiques (10 bandes fleuries et six bandes enherbées semées) d'un domaine agroécologique expérimental (125 ha). Ces espèces à phénologie de floraison contrastée présentent toutes deux une longue période de floraison avec des variations intraspécifiques qui déterminent l'exposition des individus aux interactions plantes‐pollinisateurs et aux conditions météorologiques. Nous avons appliqué une approche phénologiquement explicite centrée sur l'individu végétal, de manière à relier précisément la période de floraison de chaque individu aux niveaux correspondants d'hétérogénéité spatio‐temporelle des interactions plantes‐pollinisateurs, des densités de donneurs de pollen potentiels, des ressources florales (aux échelles de l'individu végétal, de l'assemblage local et du réseau d'interactions des infrastructures écologiques à travers la ferme) et des conditions abiotiques (température, précipitations, azote). L'attractivité individuelle (offre florale et taux de visite par les pollinisateurs) ainsi que la densité florale (toutes espèces) dans l'assemblage interspécifique local ont affecté positivement la production individuelle de graines des deux espèces végétales. Celle de C. jacea augmentait aussi directement avec la densité d'individus conspécifiques fleuris dans l'assemblage local. La densité de couplage du réseau a affecté positivement la production individuelle de graines des deux espèces et a influencé celle de C. segetum en modifiant l'effet de l'assemblage local (richesse et densité florales, richesse spécifique de pollinisateurs potentiels) sur le nombre de graines par individu. Le succès reproducteur individuel de C. segetum augmentait aussi avec le niveau de dépendance mutuelle entre l'espèce et ses pollinisateurs dans le réseau. Chez C. jacea, la production de graines individuelle était maximisée quand à la fois le niveau de spécialisation de C. jacea sur ses pollinisateurs dans le réseau et sa dépendance mutuelle à ses pollinisateurs étaient élevés. Les conditions abiotiques n'ont eu qu'un impact limité voire inexistant sur le succès reproducteur. Nos résultats montrent comment l'équilibre des interactions plantes‐pollinisateurs entre espèces et individus, peut répondre à l'hétérogénéité spatio‐temporelle liée à la gestion agroécologique de différentes façons qui affectent la reproduction des plantes sauvages. Les relations entre les interactions plantes‐pollinisateurs et la production individuelle de graines des plantes focales se déclinent entre et au sein de différentes échelles écologiques, de l'individu à la communauté, impliquant une co‐occurrence d'interactions facilitatrices et compétitrices entre espèces et individus de plantes via les pollinisateurs.